Recent Advances in Vaccine Technology for Viral Infection Management: A Spotlight on Next-Generation Vaccines and Nucleic Acid-Based Platforms - Muhammad Zahid Ali, Yousra Anwar, Adil Abbas, Noor Ul Ain, Zainab Khalid, Arooj Sattar, Muhammad Usman, Arzoo Nazir, Shah Zeb, (Pakistan Journal of Medical & Health Sciences, 2023)
Recent advances in vaccine technology and their uses in viral infection management were the focus of the study. Potential nucleic acid-based platforms for vaccine development, including DNA and RNA vaccines, were also investigated. During the COVID-19 pandemic, a lot of attention was paid to RNA-based vaccinations like mRNA vaccines because of their rapid development and scalability. These vaccines were shown to be effective at eliciting protective immune responses and provided the adaptability to include multiple antigenic sites. Preclinical and clinical research of this magnitude is required for the development and assessment of these innovative vaccine methods. Immunogenicity, side effects, and efficacy were all taken into account. The study highlighted the need for more investigation and cooperation between researchers, physicians, and business allies to speed up the process of turning these novel vaccine strategies into successful therapies against different types of viral infections. Our study demonstrated the potential of viral vectors, nanoparticles, and nucleic acid-based platforms in developing vaccine technology, and it contributes important insights into the design and evaluation of innovative vaccine tactics against viral diseases. These results add to the existing body of knowledge and may help direct future antiviral research and development. Keywords: Vaccine development, Viruses, DNA Vaccines, RNA Vaccines, COVID-19 Vaccines